Rotaviruses Methods and Protocols - Gray, James; Desselberger, Ulrich; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2000)
In Rotaviruses: Methods and Protocols, James Gray and Ulrich Desselberger have assembled a comprehensive collection of established and cutting-edge methods for studying and illuminating the structure, molecular biology, pathogenesis, epidemiology, and prevention in animal models of infection with rotaviruses, an important cause of infant morbidity and mortality. Presented by experts in the fields of animal and human rotavirus infections and rotavirus vaccine research, these readily reproducible methods detail molecular and other modern techniques, and include relevant background information and various notes to ensure reproducible and robust results. Authoritative and up-to-date, Rotaviruses: Methods and Protocols offers researchers today's benchmark compendium of experimental methods for the investigation of this medically significant virus.
Rotaviruses: Basic Facts -- Electron Cryomicroscopy and Computer Image Processing Techniques -- Virus Replication -- Rotavirus Entry into Tissue Culture Cells -- Mixed Infections with Rotaviruses -- Pathogenesis and Animal Models -- Immunologic Methods and Correlates of Protection -- In Vivo Study of Immunity to Rotaviruses -- Evaluation of Rotavirus Vaccines in Small Animal Models -- Methods of Rotavirus Detection, Sero- and Genotyping, Sequencing, and Phylogenetic Analysis -- Epidemiology of Group A Rotaviruses Surveillance and Burden of Disease Studies -- Future Rotavirus Research.
Keywords: Virology; Virology